From the limit of urbanization to the limit of the urban: the territorial configuration of greater Paris and greater Madrid (1910-1939) (Ciudades, 2017)
Town planning practice and discourses experienced a parallel evolution in Madrid and Paris during the first decades of 20th Century. International models and tools were adapted to the local context and to the new challenges of the greater city. Although the transformations of town planning were remarkable in both cities, they can be better understood as a gradual evolution rather than a rupture. The comparative and evolving analysis of Paris and Madrid planning history and its connections with social and political dynamics outlines new pathways for future research from a transnational perspective. The study of the evolution of planning in two cities with common references allows not only discovering similarities, but mainly to observe differences and alternative paths.The idea of city limit helps to better comprehend the gradual construction of two urban planning and political cultures as well as the collective narrative of the Greater city, between 1910 and the Second World War.
Keywords: urban planning; urban cultures; transfers; Paris; Madrid